PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN BERPIKIR KRITIS DAN PRESTASI BELAJAR - Evi Yuniarsi; Johanes Sapri (DIADIK, 2022)
This  research  aims  to  describe application  of  the  Problem Based Learning (PBL) model  which can improve the critical thinking and the learning achievement.  The  method  used  in the types of research carried out were Classroom Action Research (CAR) and quasi-experiments . The subjects of this research were students of class VIII  SMP Negeri 2 Merapi Barat in semester 2 of the 2020/ 2021 academic year. The number  of  students  for  the CAR class is 32 people, for the Experiment class 31 people, and for the Control class 30 people. The data collection method in this research used the Problem Based Learning (PBL) model observation sheet, observation  sheet  on  students' critical thinking and learning outcomes tests. The  data  analysis used an average score and a test which consisted of  a  different   test  between  cycles  and  a  two-sample  difference  test  that was not related. The results showed that the application of the Problem Based Learning (PBL) model could improve critical thinking, learning achievement and the effectiveness of student learning outcomes in Indonesian class VIII  SMP Negeri 2 Merapi Barat